PENDAMPINGAN MANAJEMEN SERTIFIKASI HALAL PADA UMKM MAKANAN KHAS BANYUMAS - Triani Arofah; Wita Ramadhanti; Nur Aini; Dian Purnomojati; Oman Rusmana (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2023)
The purpose of this service is to provide understanding and assist in the management of halal assurance certification to SMEs. The method of this activity is observation, interviews, and documenting selected SME data. Mentoring activities are carried out face-to-face. The results of observations and interviews with 3 food and beverage SMEs resulted in several conclusions, namely: the halal certification program is known by all SMEs, but most are not interested in taking care of certification for reasons such as: 1) still prioritizing time to sell rather than participating in socialization about halal assurance; 2) the management of halal certification isstill considered complicated and confusing; 3) does not have the funds to administer the certification; 4) because they don't want to take care of the halal guarantee of their products. Judging from the understanding/cognitive aspect, SMEs feel that halal certification is very important, it means that understanding and knowledge of good halal certification is not enough to increase the interest of SMEs in obtaining halal assurance certification. Therefore, the service team will assist in the management of halal assurance certification by first the requirements for its management, including kitchens that must meet hygiene requirements according to halal certification or kitchen floors that are in accordance with the requirements, SMEs assisted are Getuk Goreng “Tela Asli”, Cireng “Trijaya” and Kecombrang syrup “Honje Laka Syrup” Beverage. Assistance is carried out in 2 stages, namely: (1) training of halal driving cadres, and (2) handling halal certification documents. It is hoped that this halal certification service activity can provide added value so that it can increase sales of MSME products.